STRATEGI IMPLEMENTASI KEBIJAKAN PEMERINTAH DESA DALAM MENUNJANG KEBERHASILAN BADAN USAHA MILIK DESA (BUMDES) DESA KUTA - Zusana Santi Naha Maramba Djua; Annisa Purwatiningsih (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
According to Law Number 6 of 2014 concerning Villages, it is explained that Village is a legal community unit that has territorial boundaries authorized to regulate and manage government affairs. One of the government policies to make it easier for villages to manage their existing potential is that village governments are encouraged to have Village-Owned Enterprises (BUMDes). The success of Village-Owned Enterprises is on the shoulders of the government in the village itself. In the existing program implementation strategy, the village government must understand the local village situation and must be ready to improvise with any changes in the situation without ignoring the goals that have been previously set. A factor or variable does not determine the success of Village-Owned Enterprises. However, it is determined and influenced by various existing factors, such as the village government's need for a helpful policy strategy to succeed in an existing program. Implementing existing programs must be done professionally and transparently. The research method was descriptive qualitative using a purposive sampling technique. The research results proved that Village-Owned Enterprises has not been entirely successful because only a few programs have just been implemented. Additionally, the village government used several strategies, including program strategies, strategies for increasing supporting resources, and organizational strategies.